OsPSKR15, a phytosulfokine receptor from rice enhances abscisic acid response and drought stress tolerance. Issue 1 (1st October 2021) - Nagar, Preeti; Sharma, Namisha; Jain, Muskan; Sharma, Gauri; Prasad, Manoj; Mustafiz, Ananda
Abstract: Abscisic acid (ABA) is a major phytohormone that acts as stimuli and plays an important role in plant growth, development, and environmental stress responses. Membrane‐localized receptor‐like kinases (RLKs) help to detect extracellular stimuli and activate downstream signaling responses to modulate a variety of biological processes. Phytosulfokine receptor (PSKR), a Leu‐rich repeat (LRR)‐RLK, has been characterized for its role in growth, development and biotic stress. Here, we observed that OsPSKR15, a rice PSKR, was upregulated by ABA in Oryza sativa . We demonstrated OsPSKR15 is a positive regulator in plant response to ABA. Ectopic expression of OsPSKR15 in Arabidopsis thaliana increased the sensitivity to ABA during germination, growth and stomatal closure. Consistently, the expression of ABA‐inducible genes was significantly upregulated in these plants. OsPSKR15 also regulated reactive oxygen species (ROS)‐mediated ABA signaling in guard cells, thereby governing stomatal closure. Furthermore, the constitutive expression of OsPSKR15 enhanced drought tolerance by reducing the transpirational water loss in Arabidopsis. We also reported that OsPSKR15 directly interacts with AtPYL9 and its orthologue OsPYL11 of rice through its kinase domain in the plasma membrane and nucleus. Altogether, these results reveal an important role of OsPSKR15 in plant response toward abiotic stress in an ABA‐dependent manner.